CO2 laser therapy for cervical intraepithelial neoplasia - Caglar, H; Ayhan, A; Hreshchyshyn, M M (Gynecologic oncology, 1985)
One hundred and fifty-six patients with cervical intraepithelial neoplasia (CIN) were treated with CO2 laser and followed for 2 1/2 to 6 years. There were 19 recurrences, of which 14 occurred in patients treated with a power density of less than 1000 W/cm2 to a depth of 6 mm. All of the recurrences were subjected to a second laser treatment. Overall failure rate was 4.5%. The incidence of acute bleeding during, and late bleeding 6 to 14 days following treatment, were 8 and 4%, respectively. Late bleeding occurred in patients who were treated with 800 to 1000 W/cm2 power density and to a 3 to 10 mm depth of destruction. Complications were directly and failures were inversely proportional to the power density and depth of destruction. Following therapy, the transformation zone was adequately seen in the majority of the patients.